(untitled) (Journal of Rangpur Medical College, 2024)
Background: Psoriasis is a common autoimmune disorder with regional and ethnic differences in its prevalence and clinical manifestations. It is known to be associated with the presence of certain specific Human Leukocyte Antigen (HLA) alleles and characterized by T cell-mediated keratinocyte hyperproliferation. Genetic factors are also important in both susceptibility to and the expression of psoriatic arthritis. A significant portion of psoriatic arthritis patients develop psoriasis after arthritis manifestation. So, it may be helpful if we could identify the HLA alleles involved in patients with psoriasis and in patients with psoriatic arthritis. Through the HLA alleles pattern, we can identify those psoriatic arthritis patients earlier who develop arthritis manifestations without psoriasis and treat them appropriately. Objective: To detect HLA-B and HLA-C alleles that may contribute to the genetic susceptibility to psoriasis in Bangladeshi patients. Methods: This cross-sectional study was carried out on patients with psoriasis in outpatient department of Rheumatology, outpatient department of Dermatology, department of Microbiology and Immunology, Bangabandhu Sheikh Mujib Medical University from March 2015 to April 2017 on 33 patients diagnosed as psoriasis clinically by both rheumatologist and dermatologist compared with 30 controls having no history or family history of psoriasis. Results: In this study we found that there are increased frequencies of HLA-B*57 (39.4%, OR-1.4, P=0.52), B*35 (21.2%, OR-1.04, P=0.9), B*44 (18.2%, OR-1.05, P=0.87) and C*6 (18.2, OR-1.05, P=0.87) in psoriatic patients. These alleles were also identified in increased frequency in control subjects. Conclusion: HLA-B*44, B*57, B*35 and C*6 and C*7 alleles were detected in increased frequency in psoriatic patients although these were also frequent in normal subjects. It needs a further study which includes a large sample size to find out association with psoriasis. J Rang Med Col. September 2024; Vol. 9, No. 2: 3-7